A Psychological Analysis of Students' Self-Efficacy in Learning: A Comparative Study between Indonesian and Egyptian High School Students - syafii, hisyam; Azhari, Husain (South Sulawesi Education Development, 2025)
Academic self-efficacy plays a critical role in shaping students' academic performance and resilience. This study aims to compare the academic self-efficacy of high school students in Indonesia and Egypt, focusing on how contextual factors such as education systems and cultural norms influence this psychological construct. A quantitative cross-country comparative method was employed, involving 100 students (50 from Yogyakarta, Indonesia, and 50 from Cairo, Egypt) selected using proportional stratified random sampling. Data were collected using the Academic Self-Efficacy Scale, validated for cross-cultural contexts, and analyzed using independent sample t-tests, MANOVA, and SEM techniques.The results reveal that Indonesian students scored significantly higher across all dimensions of academic self-efficacy. For instance, the